Potential of Kecombrang (Etlingera elatior) Flower Ethanol Extract as an Anti-Bacterial for Escherichia coli and Pseudomonas aeruginosa in Urinary Tract Infection Patients - Zahra, Angelique Fadhilah; Silviani, Yusianti (Jurnal Biologi Tropis, 2025)
Pseudomonas aeruginosa and Escherichia coli are the two bacteria that produce one of the most prevalent urinary tract infections (UTIs). The rising resistance to antibiotics in these bacteria has led to the need for alternative treatments. Using natural materials, such as torch ginger flowers (Etlingera elatior), which are known to possess potent antibacterial chemicals, is one such option. This study aimed to determine the effectiveness of ethanol extract of torch ginger flower against Escherichia coli and Pseudomonas aeruginosa, and to compare its performance with ciprofloxacin as a standard control. The study was designed using a cross-sectional experimental method. The disk diffusion method on Mueller-Hinton Agar was used to assess the extract's antibacterial activity after it was made by macerating it with 70% ethanol. With an average inhibition zone of 7.8 mm against Escherichia coli and 8 mm against Pseudomonas aeruginosa at a 100% concentration, the findings demonstrated the antibacterial activity of Etlingera elatior's ethanol extract. These inhibition zones, however, were much smaller than those of ciprofloxacin, which had respective measurements of 10 mm and 34 mm. Significant differences between the extract concentrations were found by statistical analysis using the Kruskal-Wallis and Mann-Whitney tests (p < 0.05). In conclusion, the ethanol extract of torch ginger flower shows potential antibacterial activity against UTI-causing bacteria, although its effectiveness is not yet comparable to ciprofloxacin. Further research is needed to improve extraction methods and develop more effective formulations to enhance its antibacterial properties.